Seasonal 25-hydroxyvitamin D levels in new childhood-onset SLE: associations with disease activity and peripheral lymphocyte subsets - Chenxi Wei; Shufeng Zhi; Jiayin Li; Lijun Jiang; Xue Zhao; Qingxiao Su; Xingjie Qi; Hui Zhao; Zanhua Rong (Lupus Science & Medicine, 2026)
Objective This study aimed to compare 25-hydroxyvitamin D (25-(OH)D) levels and peripheral lymphocyte subsets between children with new childhood-onset SLE and healthy controls across different seasons, and to explore the relationships of seasonal 25-(OH)D concentrations with the disease activity and peripheral lymphocyte subsets in paediatric patients with SLE. Methods A retrospective study was conducted, enrolling 285 patients with new childhood-onset SLE and 175 healthy children. All participants were divided into a winter-spring group and a summer-autumn group according to sampling seasons. Serum 25-(OH)D levels and peripheral lymphocyte subsets were detected and quantified. Results Compared with healthy controls, patients with SLE presented with significantly higher proportions of CD8 + T cells (p